Evaluation of the Physical Stability of Body Butter Containing Cocoa Peel Extract (Theobroma cacao L.) - Muzdalifah Rizqa R Hanapi; Febrianika Ayu Kusumaningtyas; Ria Rezki Botutihe (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Skin is the outermost part of the human body that interacts directly with the environment, which is one of the risk factors that cause dry skin. Brown skin (Theobroma cacao L.) contains one of the compounds, namely polyphenols which are grouped as a type of flavonoid that can protect the skin from compounds that cause dry skin, sides, dullness, and wrinkles. This study aims to formulate body butter with variations in the concentration of 1% (F1), 3% (F2), 5% (F3) chocolate skin extract which is then tested for physical properties including organoleptical, pH, homogeneity, spreadability, adhesion, and stability using centrifugation. The results showed that cocoa bark extract (Theobroma cacao L.) body butter preparation was not stable in storage for approximately 1 year but remained stable in storage for less than 6 months.